O uso de jogos e desafios no ensino de lógica matemática. (2005)
This paper is a result of my work as a professor of Logical Mathematics in teachíng of undergraduate students. It is a  direct result of my concem ofhow this discipline develops in classes. Due to its very formal approach there have been gaps in the way  the logical and deductive way of thinking are being developed among students. It is believed that an elaborated methodology helps overcome this discrepancy.